Unbalance fault location in electrical distribution system - Faradonbeh, M.A.; Mokhlis, Hazlie (IEEE, 2011)
Fast fault location in distribution system is very important to improve the reliability of power supply. Once a fault has been cleared, fault need to be located before restoration can be conducted. By having a fast fault location method, outage time can be reduced. This research outlines some existing methods and its application in determining the location of a fault on ac distribution lines. The studies methods are Reactive component method, Takagi method, Richards and Tan method, Srinivasan and St-Jacques method, Girgis method and Das method. However, in this research part of Das method is applied to locate a faulted section due to its simplicity and economical in distribution system. The proposed method is tested using Saskpower distribution system of Sask State from Canada. The system is modeled using power system PSCAD/EMTDC power system simulator. Fault is simulated at various locations and the voltage and current measurements at the primary substation is used to calculate apparent reactance. Then, the apparent reactance is compared with line reactance to find the faulted section. The tests have been conducted at few locations to study the effectiveness of the proposed method. Besides, different fault types were also been tested. Overall, the test shows promising results.